Optimizing IDX 80 Stock Portfolio Using Single Index Model for Efficient Investment Strategy - Putri Ulfa, Yunita; Sugi Lestari, Ni Luh Ketut; Janiantari, I Gusti Ayu (Moneter: Jurnal Keuangan dan Perbankan, 2025)
This study evaluates the effectiveness of the Single Index Model in forming an optimal stock portfolio using IDX80 index constituents from January 2021 to January 2025. Using a quantitative descriptive approach and purposive sampling, 42 consistently listed stocks were selected. Secondary data were sourced from the IDX, Yahoo Finance, and Bank Indonesia. Each stock’s return, beta, alpha, and residual variance were calculated, and stocks with Excess Return to Beta (ERB) values above the cut-off point (C*) were selected. The results identified seven optimal stocks: MAPI, ITMG, AKRA, MEDC, ADRO, BMRI, and BBNI. The resulting portfolio achieved an expected return of 1.82% with a low risk level of 0.11%, indicating investment efficiency. The findings demonstrate that the Single Index Model is a practical and effective tool for portfolio construction, especially for millennial and Gen Z investors seeking structured, data-based investment strategies amid digital market trends and shifting investor demographics.